Pengembangan Aplikasi Android Presensi Kehadiran Realtime menggunakan Pengenalan Wajah dengan Model Facenet - Natanniel Eka Christyanto; Eriq Muhammad Adams Jonemaro; Novanto Yudistira (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Attendance system is a system that regulates the presence or presence (a person, a group of people) at a place. There are various methods that can be done in recording attendance, namely the signature method, fingerprint method, card method, face recognition method, and so on. These various methods have their respective weaknesses and advantages, and the selection of methods can be adjusted to the prevailing conditions and situations. The Presence System application created has the aim of making it easier to take attendance without making direct contact with the tool quickly and integrated with the web to display attendance status in real time. This application is designed using Android because the use and availability of devices that use Android is very wide and available in various circles of society. Taken from one source of survey of the use of the Android Operating System (OS) states that 70% still use Android worldwide. In this research, the application is made using the Kotlin programming language on Android, web platform development using the Bubble.io tool, and PHP and SQL programming languages as supporting databases that contact Android devices with websites. Based on the results of the tests carried out, testing the Functional Suitability characteristics scored 100%, Compatibility characteristics with a score of 93.75%, Reliability characteristics with a score of 100%, and face recognition accuracy with a score of 100%.